Process using Laser Method on 3-Phase Induction Motor and Spray Washing Pump to Overcome Misalignment - Dodi, Nofri; Abadi, Akbar; Septiani, Yudia Meka; Widia, Riza; Ardhi, Ardiansyah (LPPM Universitas Andalas, 2025)
The alignment process using the laser method is one of the alignment techniques that can be applied to address misalignment. The laser method operates by utilizing an infrared laser sensor to perform the alignment between the driving object, in this case the induction motor, and the driven object, namely the spray washing pump. The alignment process aims to align the shaft of the driving object (the induction motor) with the shaft of the driven object (the spray washing pump), ensuring that both shafts are properly aligned. Misalignment refers to a condition in which there is a lack of alignment between the driving shaft and the driven shaft.